EFEK MEDIASI MOTIVASI BELAJAR PADA PENGARUH ADVERSITY QUOTIENT TERHADAP HASIL BELAJAR SISWA - F Kusnanda; I Waspada; K G Hilmiatussaidah; N Istikomah (Jurnal Pendidikan Ekonomi Indonesia, 2022)
This research is based on the results of student learning in economic subjects that haven’t reached the Minimum Completion Criteria (KKM) which is shown by the average results of the Final Semester Assessment (PAS) for 2018/2019 school year of public Senior High school in Bandung City. The purpose of this study was to determine the effect of Adversity Quotient on student learning outcomes in economic subjects in class XI Public Senior High school in Bandung City with learning motivation as a mediating variable. The research method used is an explanatory survey using a questionnaire as a data collection tool. The population in this study were students of class XI IPS public Senior High School in Bandung as many as 2,403 students. By using a random sampling technique, a sample of 610 students was obtained. The data analysis technique used is the regression test of the causal step strategy: Baron Kenny. The results showed: (i) The level of Adversity Quotient and learning motivation was in the sufficient category while there were still many students who obtained learning outcomes below the minimum completeness criteria (KKM); (ii) Adversity Quotient has a positive and significant effect on learning outcomes; (iii) Adversity Quotient has a positive and significant effect on learning motivation; (iv) Motivation to learn partially mediates the influence of Adversity Quotient on learning outcomes.